Trafficking in human organs in Europe - Meyer, Silke (Henry Stewart Talks, 2008)
Trafficking in organs, Myths vs. actual threats, Illicit sale and purchase of human organs, especially kidneys, Circumvention of official waiting lists and national as well as international transplantation legislations, Involvement of organized and white collar crime, Donor and destination countries
Archived at 2022/04/03